The Effect Of The Problem-Based Learning Model With The Picture And Picture Approach Based On Flashcard Media On Literacy Ability And Thematic Learning Outcomes Of Fifth Grade Students - Taming, Rida Warda; Musbaing, Musbaing; Taufik, Ashabul (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2026)
Learning is the core of education. The effectiveness of the learning process is greatly determined by the strategies applied. Therefore, this study aims to examine the effect of the PBL (Problem Based Learning) model integrated with the Picture and Picture approach using Flashcard media on the literacy skills and thematic learning outcomes of fifth-grade students at SD Inpres Tamalanrea III Makassar. This research experimental and involved a total of 21 fifth-grade students. Data collection techniques included observation of student and teacher activities, documentation, as well as pre-tests and post-tests. Quantitative data analysis revealed two important findings. First, the implementation of PBL using the Picture and Picture approach based on Flashcards showed an effect on students' literacy skills. This is evidenced by an increase in the average score (from 57.14 to 89.14) and the hypothesis results with Sig. = 0.000. Second, this model also shows an influence on students' thematic learning outcomes, as evidenced by the increase in the average score (from 60.19 to 88.24) with the same hypothesis test result, namely Sig. = 0.000. Overall, this strategy has been proven effective in overcoming learning fatigue and enhancing students' active participation, which is key to improving literacy skills and learning outcomes.